Study of Resilience in Learning Environments During the Covid-19 Pandemic - Raghunathan, Shriram; Darshan Singh, Abtar; Sharma, Bibhya (Frontiers in Education, 2022)
The Covid-19 pandemic has caused a great change in the world. One aspect of the pandemic is its effect on Educational systems. Educators have had to shift to a pure online based system. This shift has been sudden and without any prior warning. Despite this the Educational system has survived and exhibited resilience. The resilience of a system can be determined if the system continues to operate or function as effectively as before a change. Resilience in a system implies the ability to work and develop when the forces in the environment are unexpected, abrupt and sudden as well. The environment may change or evolve but the underlying system must keep functioning, developing and responding. Resilience is a trait in a system. It is a set of characteristics in the system that enables it to sustain itself in the face of change. A resilient system can cope and prosper in the face of change. For the domain of education, the Covid-19 pandemic served as a phenomenal change event and a wakeup call to the education fraternity. As a social system, resilience meant that the people in the educational environment continued to function albeit differently. The environment, meaning the processes, hierarchy and the intricate social ties in the system contributed to the resiliency of the system. Thus the measure of resilience in education has three major facets—people, the technology which facilitates the process and the process environment. This work aims to understand the resilience of the teachers due to the Covid-19 pandemic, especially how learning continued and what contributed to this continuity. Resilience research and understanding is as important as the pedagogical and technological aspects in an Educational system as it is a trait that encompasses the people, the socio-economic system and their relationships. In this work, we analyzed resilience as trait, its relevance in an Educational system, factors that make up resilience in an Educational system and finally the relevant research about resilience in Education during Covid-19. Based on the results of our literature review we formed a model for Educators. A survey was conducted among educators of three countries namely Malaysia, Fiji, and India to determine the essential elements of resilience that were relevant to the continuity of an educational system from the point of view of teachers. We arrived at a set of factors that are relevant to the teachers in the educational systems which can be an impetus for policy makers to focus on and develop. The major results from the study are the need for Educational systems to focus on three facets—internal, interpersonal and external aspects of teachers and strengthen factors such as support for teachers, strong academic leadership, trust of teachers, increase self-motivation, enhance communication with stakeholders and emphasize systems that enhance student-teacher communication. The future areas of research are also discussed in the work.